2015
DOI: 10.3109/00365521.2015.1033745
|View full text |Cite
|
Sign up to set email alerts
|

Alarm symptoms of upper gastrointestinal cancer and contact to general practice – A population-based study

Abstract: The specific alarm symptoms of upper GI cancer are not very prevalent in the general population. The proportion of GP contacts with each of the four specific symptoms varied between 24.3% and 39.9%. The proportion of GP contacts was higher in the older age and with combinations of two symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…40 Conversely, repeated vomiting is 1 of the symptoms used to diagnose upper digestive cancer, because it is considered an alarm symptom. 41 In our study, vomiting also was the most prevalent NIS in patients with upper digestive cancer.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…40 Conversely, repeated vomiting is 1 of the symptoms used to diagnose upper digestive cancer, because it is considered an alarm symptom. 41 In our study, vomiting also was the most prevalent NIS in patients with upper digestive cancer.…”
Section: Discussionsupporting
confidence: 53%
“…Nausea was higher in patients with gynecological cancer, and similar findings were reported in a conductive study at Aga Khan University Hospital, Pakistani, where 1 of the most common adverse effects was nausea (33.3%) in patients who received pelvic radiotherapy for gynecological cancer . Conversely, repeated vomiting is 1 of the symptoms used to diagnose upper digestive cancer, because it is considered an alarm symptom . In our study, vomiting also was the most prevalent NIS in patients with upper digestive cancer.…”
Section: Discussionmentioning
confidence: 48%
“…The guidelines give access to fact track endoscopy for patients presenting specific alarm symptoms indicative of upper GI cancer such as blood in vomit and new onset dyspepsia in individuals over 45 years. We have previously reported that specific alarm symptoms of upper GI cancer are not very prevalent in the general population [ 6 ]. Much of the evidence supporting referral guidelines derive from secondary care settings and patients already diagnosed with upper GI cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Respecto a los síntomas, los más frecuentes encontrados para el CG fueron náuseas y vómito (52%), y dolor epigástrico (50%), lo cual fue similar a los reportados por varios autores, destacando que existen reportes superiores al 80% para dolor abdominal o epigástrico [8,11,13,14,16,17,18]. Sobre pérdida de peso, la frecuencia reportada fue del 31% de los pacientes, lo cual difiere a lo encontrado por otros autores de Estados Unidos [14], Dinamarca [19], Polonia [20] y Reino Unido [14]. En Colombia existía un estudio previo que la reportó en el 83% de los casos [12].…”
Section: Discussionunclassified